2019
DOI: 10.1007/s11605-018-3948-x
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Outcomes for Perihilar Cholangiocarcinoma with Vascular Invasion

Abstract: Short-term outcomes for patients with perihilar cholangiocarcinoma and undergoing vascular resection were poor compared to those without vascular resection. Long-term survival in R0M0 disease was more favorable; aggressive surgery is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 39 publications
0
25
0
Order By: Relevance
“…Even though a few studies have reported that perioperative outcomes such as perioperative blood transfusion were poor prognostic factors for long-term survival, 12 most studies have revealed tumor-related factors such as lymph node metastasis, R1 resection, high preoperative carcinoembryonic antigen level, poor differentiation, and vascular invasion as independent risk factors for long-term survival after curative treatment of HCCA. 5,[12][13][14][15][16][17][18][19][20][21] Therefore, improved perioperative outcomes might not necessarily improve the long-term survival outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Even though a few studies have reported that perioperative outcomes such as perioperative blood transfusion were poor prognostic factors for long-term survival, 12 most studies have revealed tumor-related factors such as lymph node metastasis, R1 resection, high preoperative carcinoembryonic antigen level, poor differentiation, and vascular invasion as independent risk factors for long-term survival after curative treatment of HCCA. 5,[12][13][14][15][16][17][18][19][20][21] Therefore, improved perioperative outcomes might not necessarily improve the long-term survival outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…For such advanced PHC, major hepatectomy combined with arterial and portal resection remains the only possibility for obtaining negative margins, although in some earlier studies, it showed higher mortality rates compared to hepatectomy without vascular resection [3][4]. Currently, experience and advances in complex hepatic and vascular surgical techniques have led to more aggressive approaches with acceptable outcomes [1,3,5]. Nagino et al reported a large series of 50 combined arterial and portal resections with a perioperative mortality of 2%.…”
Section: Discussionmentioning
confidence: 99%
“…Vascular invasion is related to more advanced disease and is known as a poor prognostic factor. However, compared to unresectable tumors or resection with positive margins, combined portal vein and hepatic artery resection offers improved survival when feasible [1,[3][4][5].…”
Section: Discussionmentioning
confidence: 99%
“…Among them, 88 records were further excluded for the following reasons: not in English (n = 7); abstract form only (n = 38); contained other malignancies or benign tumors (n = 2); reconstruction or no reconstruction as comparison item (n = 2); inadequate data (n = 7); and case reports (n = 32). Finally, 22 studies (Higuchi et al, 2019;Mizuno et al, 2020;Schimizzi et al, 2018;She et al, 2020;Yu et al, 2017;Peng et al, 2016;Miyazaki et al, 2007;Nagino et al, 2010;De Jong et al, 2012;Dumitraşcu et al, 2017;Igami et al, 2010;Klempnauer et al, 1997;Kondo et al, 2004;Lee et al, 2010;Matsuyama et al, 2016;Muñoz et al, 2002;Song et al, 2009;Tamoto et al, 2014;Wang et al, 2015) including 4091 PHC patients were eligible for this systematic review and meta-analysis.…”
Section: Literature Searchmentioning
confidence: 99%
“…Therefore, to achieve R0 resection, vascular resection (VR) can be performed during the operation. It has been reported that the proportion of VR during PHC surgery ranges from 15% to 38% (Higuchi et al, 2019;Mizuno et al, 2020;Schimizzi et al, 2018;She et al, 2020;Yu et al, 2017). VR refers to portal vein resection (PVR), hepatic artery resection (HAR) or both.…”
Section: Introductionmentioning
confidence: 99%